Fitz-Hugh–Curtis Syndrome in an Adolescent Athlete: MRI Diagnosis of an Atypical Presentation: Fitz-Hugh–Curtisov sindrom pri adolescentki: zapoznela diagnoza subtilne klinične slike - Čokolič, Eva; Lučič Šrajer, Lucijan; Kodrič, Ivana; Dobnik, Sarah; Žerdin, Matija; Sefić Pašič, Irmina (Acta Medico-Biotechnica, 2025)
Purpose: To emphasize the diagnostic role of magnetic resonance imaging (MRI) in identifying Fitz-Hugh–Curtis syndrome (FHCS) in an adolescent patient with a subtleclinical presentation.Methods: A 17-year-old female presented with acute onset right upper quadrant and right shoulder pain. The initial diagnostic workup, including ultrasound (US), computedtomography (CT), and laboratory testing was inconclusive. Due to persistent symptoms and elevated inflammatory markers, MRI of the abdomen and pelvis was subsequentlyperformed.Results: MRI demonstrated a bilateral pyosalpinx with restricted diffusion, free fluid in the pelvis and subhepatic region, and linear adhesions between the hepatic capsule and peritoneum, which was consistentwith pelvic inflammatory disease (PID) complicated by FHCS. Microbiologic analysis confirmed a Chlamydia trachomatis infection. The patient received targeted antibiotic therapy with clinical improvement.Conclusion: FHCS represents a rare but importantcomplication of PID that may present with non-specificor extra-pelvic symptoms. MRI is the modality of choicefor confirming PID-related complications and perihepatic inflammation, offering high sensitivity and the advantage of radiation-free imaging, which is especially relevant in the adolescent population.
Keywords: Fitz-Hugh-Curtis syndrome; PID; MRI; Chlamydia infections; Shoulder pain